مساهمة في دراسة توزع المركبات الهيدروكربونية العطرية (PAHs) في رسوبيات ومياه شاطئ مدينة بانياس - محمد عصام; علاء الدين فاتن; محفوض هند (Latakia University Journal -Basic Sciences Series, 2018)
تناولت هذه الدراسة تحديد تراكيزمركبات الـ (PAHs) في رسوبيات وميـاه شاطـئ مدينة بانياس، شملت ستة مواقع ابتداءً من عرب الملك شمالاً ، حتى الفنار جنوباً ، خلال الفترة الممتدة من أيار2000 إلى حزيران 2001 . تم التحري عن 19 مركب من مركبات الـ (PAHs) بالاعتماد على تقانة الكروماتوغرافيا الغازية وباستخدام كاشف تشرد اللهب (FID)، وأظهرت النتائج وجود تراكم للمركبات الهيدروكربونية العطرية في رسوبيـات هـذه المنطقة، حيث سـجلت أعلى قيمـة لـ (ΣPAHs) (3.931µg/g) في المحطـة المقابلـة لمجرور مصفاة بانياس، وأخفض قيمـة (0.313µg/g) في محطة الفنار. من ناحية أخرى قمنا بمحاولة تحديد مصادر التلوث المحتملة بمركبات الـ (PAHs) في رسوبيات ومياه المنطقة المدروسة بالاعتماد على مؤشر Fluoranthene/Pyrene. بينت النتائج التي تم التوصل إليها انخفاض التقارب في تراكيز هذه المركبات في العينات الرسوبية لجميع المحطات خلال فترة الدراسة بالمقارنة مع القيمة العظمى(4000ng/g) لمجال التأثيرات الضعيفة (ER - L) الصادرة عن الإدارة الوطنية الأمريكية لمراقبة المحيطات والغلاف الجوي (USNOAA). This study deals with the determination of(PAHs) concentrations in sediments and coastal water of Banias city, and coveres six sites from (Arab Almalek) in the north, till(Alfanar) in the south, during the period from May 2000 to June 2001. Investigations included 19 compounds of (PAHs), employing the Gas Chromatography technique (GC), and a flame ionization detector (FID). Results revealed accumulation of (PAHs) in the sediments of this area, where the highest concentration of total PAHs (3.931µg/g) was reported in the station opposite to Banias refinery sewage system, and the lowest value (0.313µg/g) in the Alfanar site. On the other hand, we made investigations to determine the potential source of contamination by (PAHs) compounds in sediments and coastal water of this area, depending on Fluoranthene/Pyrene index. The reported results revealed a decrease to convergence in the concentrations of these compounds in the sedimentary samples of all sites during the study period relative to the max. value (4000ng/g) of the effects range -low (ER-L) issued by the United State national Oceanic and atmospheric administration (USNOAA).